2018
DOI: 10.24016/2018.v4n1.90
|View full text |Cite
|
Sign up to set email alerts
|

Estructura interna del Cuestionario de Evaluación de Violencia Escolar Infantil y Primaria en un entorno violento de México

Abstract: BY CrossMark click for updates RESUMENEl obje vo de este estudio es validar la estructura interna del Cues onario de Evaluación de Violencia Escolar en Infan l y Primaria en una muestra del noreste de México. Es un estudio de corte cuan ta vo y transversal. Se incluyeron, 733 niños, de los cuales, 49.8% son hombres, 50.2% mujeres, mediante un muestreo intencional, obtenido de 78 ins tuciones de educación básica de la ciudad de Sal llo, Coahuila, México. La edad promedio fue de 12 años. Los resultados confirmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These projects and evaluation instruments are born because of the increase in violence in the school context from a very early age, as reflected in the data in Mexico from the 2000 Child and Youth Consultation, carried out by the Federal Electoral Institute of Mexico (IFE). In said consultation, 32% of girls and boys between the ages of six and nine said they had been exposed to violence at school and 25% said they were the object of violence in the school environment, according to the National Health and Safety Survey [ 58 ]. Regarding adolescence, the National Survey on Exclusion, Intolerance and Violence in Public Schools at the high school level (2008) revealed that two out of ten high school students are rejected by their peers, and five out of ten accepted that they have difficulties in making friends.…”
Section: Introductionmentioning
confidence: 99%
“…These projects and evaluation instruments are born because of the increase in violence in the school context from a very early age, as reflected in the data in Mexico from the 2000 Child and Youth Consultation, carried out by the Federal Electoral Institute of Mexico (IFE). In said consultation, 32% of girls and boys between the ages of six and nine said they had been exposed to violence at school and 25% said they were the object of violence in the school environment, according to the National Health and Safety Survey [ 58 ]. Regarding adolescence, the National Survey on Exclusion, Intolerance and Violence in Public Schools at the high school level (2008) revealed that two out of ten high school students are rejected by their peers, and five out of ten accepted that they have difficulties in making friends.…”
Section: Introductionmentioning
confidence: 99%